Environmental valuation in South Asia - Haque, A. K. Enamul; Murty, M. N. (Maddipati Narasimha), 1942-; Shyamsundar, Priya, 1964- (Cambridge, UK. : Cambridge University Press, 2011)
'Provides an overview of different environmental problems in South Asia and examines how economic valuation techniques can be used to assess these problems'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Environmental economics -- Asia, South; Environmental quality -- Asia, South